ANTROPOMETRIK PENEBANG JATI DI BKPH BANDUNGSARI KPH PURWODADI PERUM PERHUTANI UNIT JAWATENGAH - Sona Suhartana; Maman Mansyur Idris (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
Anthropometric data of the workers are essential in the practice of ergonomics, especially for the design of work places, machines and equipment in order to attain work comfort and increased work productivity.Anthropometric measurements were carried out to 18 teak loggers aging between 20-35 years. The measurements included: body, shoulder, elbow and hip height; shoulder and hip width; length of arm and. hand, length of upper arm, lower arm and hand;upper reach and arm span (measurements in standing position). In sitting position, the body measurements comprised sitting, elbow, hip and knee height; length of upper and lower log.The result shoures that elbow height of teak logger has high variability and decreo,se their working comfort and productivity. Lenght of arm and hand which are longer than axe handle on the other hand speed up working fatique and infficient work.